2021
DOI: 10.1177/01937235211012178
|View full text |Cite
|
Sign up to set email alerts
|

Reifying Contemporary Versions of Liquified Racism: Black Representation in Competitive Swimming

Abstract: Throughout history, water as a tool for racialized oppression has been in constant evolution. From utilizing water as a passage to transport slaves, to using fire hoses as a form of punishment toward Black people, liquified racism is a concept we coined to represent past and present racial discrimination through the use of water. In this paper, we conducted a critical content analysis of the USA swim team and the swim team pages of the top ten Division I men’s and women’s college swimming programs to uncover h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Several scholars have defined cultural racism and its role in producing health inequities, 18, 20, 32–34 and a recent systematic review found evidence of associations between area‐level racial prejudice—a measure of cultural racism—and various adverse health outcomes 35 . However, beyond this small body of literature, empirical research explicitly operationalizing cultural racism and examining associations with health outcomes is sparse.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several scholars have defined cultural racism and its role in producing health inequities, 18, 20, 32–34 and a recent systematic review found evidence of associations between area‐level racial prejudice—a measure of cultural racism—and various adverse health outcomes 35 . However, beyond this small body of literature, empirical research explicitly operationalizing cultural racism and examining associations with health outcomes is sparse.…”
mentioning
confidence: 99%
“…Numerous authors have used the water metaphor to discuss racism, but here, we apply it specifically to cultural racism. 3,[24][25][26][27][28][29][30] As the water, cultural racism buttresses the other dimensions of racism in the production of social and health inequities. Simultaneously, cultural racism rationalizes, naturalizes, and obscures structural racism, as the murky (i.e., "darkly vague or obscure" 31 ) water surrounding the iceberg renders its base invisible.…”
mentioning
confidence: 99%
See 1 more Smart Citation